Simulation of PSD controller in Matlab - Simulink - Magdin, Martin; Koprda, Stefan (COMPUSOFT: An International Journal of Advanced Computer Technology, 2024)
A characteristic feature of all modern means of control in industry is partial to complete decentralization of the control from simple, two-level management, to fully decentralized control using LON (Local Operating Network) technologies. In all, however, is a common feature of existence dispatcher (parent) level that serving for the monitoring of technology or for its optimization in the form of human intervention in the control, With using the higher levels of control we are creating practical adaptive system able while maintaining the level of control to adapt the behavior of the entire control system current state of the technological process. This paper dealt with the analysis of PSD controller and compiling of measurement chains with using which we can regulate the temperature to the desired value.